KAJIAN SOSIOLINGUISTIK TERHADAP VARIASI BAHASA INDONESIA DALAM IKLAN TELEVISI NASIONAL - Silalahi, Maryska Debora (Smart Education, 2025)
Abstract: This study examines variations in Indonesian language found in television advertisements using a sociolinguistic approach. Sociolinguistics is a discipline that explores the relationship between language and society, including how social aspects influence language use and variation. Television advertisements are a form of mass communication with a wide reach, are persuasive, and are designed to attract public attention. Therefore, the language used in advertisements often reflects interesting variations and is appropriate to the social context of the target community. This study aims to describe the types of Indonesian language variations in television advertisements, identify the sociolinguistic causes that impact these variations, and analyze the role of language in achieving the advertisements' persuasive goals. Using a qualitative descriptive approach, data were obtained through recording, observation, and recording methods of several television advertisements broadcast on national private television channels in Indonesia. Data selection was carried out using a purposive sampling technique to obtain informative cases. Keyword: sociolinguistics; television advertising; television advertising language. Abstrak: Penelitian ini mengkaji variasi bahasa Indonesia yang terdapat dalam iklan televisi dengan pendekatan sosiolinguistik. Sosiolinguistik merupakan disiplin yang mengeksplorasi keterkaitan antara bahasa dan masyarakat, termasuk bagaimana aspek sosial mempengaruhi pemakaian dan variasi bahasa. Iklan televisi merupakan salah satu bentuk komunikasi massa dengan jangkauan luas, bersifat persuasif dan disusun untuk menarik perhatian kalangan publik. Karena itu, bahasa yang digunakan dalam iklan sering kali mencerminkan variasi menarik dan sesuai dengan konteks sosial masyarakat yang dituju. Penelitian ini bertujuan untuk menggambarkan jenis-jenis variasi bahasa Indonesia dalam iklan televisi, mengidentifikasi penyebab sosiolinguistik yang berdampak pada variasi tersebut, serta menganalisis peran bahasa dalam mencapai tujuan persuasif iklan. Dengan menerapkan pendekatan deskriptif kualitatif, data diperoleh melalui metode perekaman, pengamatan, dan pencatatan dari sejumlah iklan televisi yang ditayangkan di saluran televisi swasta nasional di Indonesia. Pemilihan data dilakukan menggunakan Teknik purposive sampling agar memperoleh kasus-kasus yang informatif. Kata kunci: sosiolinguistik; iklan televisi; bahasa iklan televisi.